Führung, wohin führst du? Wie Führungskräfte Unternehmenswerte optimieren - vergüten - bilanzieren - Habelt, Wolfgang (De Gruyter, 2012)
With this book, students receive a critical introduction to the opportunities and limits of value creation-oriented management of companies. In this way you gain a holistic picture of value-oriented corporate management. Practitioners should receive help for their own management work in order to further develop the existing action concepts, for example with the help of a so-called "value scorecard" in order to provide value-oriented corporate reporting that is more necessary than ever for employees, managers, shareholders or owners, analysts, To shape customers or suppliers.